MEDIA DAN SUMBER BELAJAR PENDIDIKAN ISLAM - Oktawira, Leni; Apriyenti, Apriyenti; Amra, Abhanda (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
This research examines media and learning resources in Islamic education which play a vital role in the Islamic learning process. In the current digital era, the development and use of effective media and learning resources is becoming increasingly important to increase students' understanding and appreciation of Islamic values. This study aims to analyze various types of media and learning resources that can be utilized in Islamic education, as well as identifying optimal use strategies in the learning process. Through a descriptive analytical approach, this research explores the potential for integrating modern technology with traditional values ​​in developing Islamic learning media that is contemporary but still in accordance with sharia principles. This research uses bibliography procedures (Library research). This method is an analysis of several references related to the research carried out, including analysis of figure views, newspapers, novels and others. In general, the tool has the benefit of clarifying notes so that they are not too verbalistic, overcoming limitations of space, duration, power and sensory energy, generating enthusiasm for practice, more direct interaction between students or students and the source of practic